Anthobium tectum Shavrin 2022, comb. nov. - Shavrin, Alexey V. (Oikos, 2022)
Anthobium tectum (Paykull, 1789) comb. nov. (Figs. 2, 46–64, 69–81) Staphylinus tectus Paykull, 1789: 68; Paykull 1800: 411, Olivier 1795: 36 Omalium tectum : Gravenhorst 1806: 213; Gyllenhal 1810: 202; Olivier 1811: 478; C. Sahlberg 1827: 278, 1830: 282; Zetterstedt 1828: 49, 1838: 50; Lacordaire 1835: 487, 1854: 142; Laporte 1840: 191 Anthobium tectum : Curtis 1829: 28; Stephens 1834: 340 Deliphrum tectum : C. Sahlberg 1830: 282; Erichson 1839: 627, 1840: 872; Heer 1839: 187; Stephens 1839: 426; Redtenbacher 1849: 750, 1857: 249, 1874: 270; Fairmaire & Laboulbène 1856: 638; Kraatz 1857: 952; Calwer 1858: 199; Thomson 1859: 50, 1861: 197; Bach 1860: 270; Fauvel 1871: 121 [= 1872: 95]; Seidlitz 1875: 236; Calwer & Jäger 1876: 172; Mulsant & Rey 1880: 117; Fowler 1888: 406; Fauconnet 1892: 121; Ganglbauer 1895: 723; Luze 1905: 245; Reitter 1909: 188; Kuhnt 1913: 189; Johansen 1914: 597; Porta 1926: 25; Portevin 1929: 442; Scheerpeltz & Höfler 1948: 153; Hansen 1952: 77; Palm 1948: 98; Lohse 1964: 51; Focarile 1978: 36; Tóth 1982: 76 Deliphrum tectum var. picipennis J. Sahlberg, 1876: 246 [unavailable name] Deliphrum ( Deliphrum ) tectum : Zanetti, 1987: 286, 2012: 65 Omalium laeve Gravenhorst, 1806: 211; Olivier 1811: 477; Stephens 1834: 352, 1839: 429 Material examined: UK: 1 ♀: ‘ Scotland D. Sharp’ (BMNH); 1 ♂: Angleterre (IRSN); NORWAY: FINNMARK: 1 ♂: Bossekop. 07.1898 (BMNH); 1 ♀: Süd-Varanger, Pasvik-Järvi. 04.1944. G. Nietsch leg (MHNG); 1♂: Vadsö. A. Strand leg. (ZMUC); 1 ♀: Lyngen. J. Sahlberg leg. (MZHF); NORDLAND: 1 ♂: Kjeldvandet, 6 km S Sulitjelma, 67º4’N 16º3’E. 510 m a.s.l. 13.viii.1961 (BMNH); 1 ♂: Tysfjord (BMNH); 1 ♀: Nordmo. 17.07.2002. Schneider leg. (MZHF); TRØNDELAG: 1 ♂, 1 ♀: Kongsvold (BMNH); TELEMARK: 1 ♀: 5 km E Kalhovd. 60º04’N 8º23’E. 900-1100 m a.s.l. 27.07.1987. Munk leg. (ZMUC); TROMS: 3 ♂♂: Tromsö (IRSN, MZHF); INNLANDET: 1 ♂, 1 ♀: Dovre, Fokstua. 07.07.1933. H. Lindberg leg. (MZHF); OSLO: 1 ♀: Christiania. M. Cameron leg. (BMNH); 1 ♂, 1 ♀: Lövstad. 15.09.1975. T.E. ...